Pre-and-postpartum managemental intervention through herbal feed supplement (Asparagus racemosus) and its effect on production and reproduction performance during supplementation and post-supplementation period in crossbred cows - KUMAR, SANTOSH; MEHLA, R K; MEENA, R K (The Indian Journal of Animal Sciences, 2011)
Shatavari (Asparagus racemosus), a medicinal plant used in Ayurveda is well documented Rasayana for its galactopoietic and therapeutic properties. Objectives of the present study were to evaluate the effects of supplementation of herbal feed supplement Asparagus racemosus (Shatavari), during prepartum to postpartum on milk production and reproductive performance of crossbred cows. Animals (10) were classified in 2 groups of 5 each, viz. C (control) and PREPOS- prepartum (i.e. 50 to 60 days dry period) to continued postpartum period (up to 90 days postpartum). During prepartum, the cows in group PREPOS were supplemented with Asparagus racemosus root powder @100 mg/kg live body weight and it was continued during postpartum period @200 mg/kg live body weight. A. racemosus supplementation during both prepartum continued to postpartum (PREPOS) resulted in significant, improvement in per day milk production and reduction in first postpartum oestrus interval, service period (day) and services per conception, and rate of uterine involution in comparison to the control group.